Computational fluid dynamics analysis and design optimization of a porous annular powder‐liquid mixer. Issue 4 (27th December 2019) - Feng, Long; Li, Zengliang; Du, Mingchao; Sun, Zhaocheng; Fan, Chunyong
Abstract: An annular powder‐liquid mixer is a new type of jet pump used to mix powder. This mixer is mainly used to mix fracturing fluids in oil and natural gas exploitation processes. Free from powder pellets, the mixer has characteristics, such as high mixing efficiency and great suction. The structural parameters, such as hose diameter, exit section diameter, falloff angle, divergence angle, hose length‐diameter ratio, and annular nozzle diameter, may influence this new type of mixer. By using an orthogonal experiment to optimize the structure of an annular ring‐type powder mixer and performing a comparative analysis of the results of numerical simulations, this paper finally determines the mixer's structure. According to experiments, the mixer's negative suction can reach 0.09 MPa, there are no powder pellets during the mixing process, and the mixing effect is very good. Abstract : In this research, a new type of fracturing fluid mixer (porous annular powder‐liquid mixer) is designed and optimized. It can mix fracturing fluids effectively and can also be used for premixing of abrasive water jets, with a wide range of applications. At the design stage in this research, the structure of the mixer is optimized to ensure the mixing effect. According to experiments, the mixer's negative suction can reach 0.09 MPa, there are no powder pellets during the mixing process, and the mixing effect is very good.